EFFECT OF CYTOPROTECTION ON THE OXIDATIVE PROCESSES AND ENDOTHELIAL FUNCTION IN ELDERLY PATIENTS WITH ISCHEMIC HEART DISEASE - A. V. Shabalin; Yu. I. Ragino; S. A. Lyubimtseva; Ya. V. Polonskaya; M. V. Ivanova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To investigate the effects of cytoprotection with mildronate (Grindex, Latvia) on oxidative processes and endothelial function in elderly patients with ischemic heart disease (IHD). Material and methods. 117 elderly (upwards 60 y.o.) patients with IHD were included into controlled study. They were also suffering from heart failure II-III functional class (according to NYHA classification) and from arterial hypertension (AH). All patients were randomized into 2 groups: 1) 67 patients (75,4±0,5 y. o.) were treated with mildronate 500 mg/day simultaneously with basic therapy during 12 weeks (the main group) and 2) 50 patients (74,0±0,6 y. o.) were treated only with basic therapy during 12 weeks (the compare group). Total cholesterol (CH), triglycerides (TG), low density lipoprotein cholesterol (LDL), high density lipoprotein CH (HDL), LDL antioxidant potential (concentration of α-tocopherol and retinol in LDL), initial level of lipid peroxidation (LPO) products in LDL, LDL resistance to oxidation and blood level of NO metabolites were determined before and after 4 and 12 weeks of the therapy. Results. Mildronate did not have any effect on the blood lipid profile in elderly patients with IHD. The initial level of LPO products in LDL was decreased by 33% and LDL resistance to oxidation was increased by 26% in the main group after 12 weeks of therapy in comparison with the same parameters before the study and in comparison with control group of patients (p<0,05). The blood level of NO metabolites was 1,4 fold higher in the main group of patients after 12 weeks of therapy in comparison with the same parameters before therapy and in comparison with control group of patients (p<0,05). More prominent growth of LDL resistance to oxidation after 12 week therapy with mildronate was revealed in men than in women, in patients with angina II class than in patients with angina III class, in patients with heart failure II class than in patients with heart failure III class. Conclusion. Some antiatherogenic effects of mildronate are observed in elderly patients with IHD. These are the decrease in LPO activity in LDL and the increase in synthesis of NO.